An Investigation of Toilet Cleanliness Assessment and People Monitoring at Rest and Service Area (R&R) X and Y - Nur Izzati Syahirah Mohd Azmi; Mohd Syafiq Syazwan Mustafa; Mohammad Ashraf Abdul Rahman; Nurdalila Saji; Mohd Fahmi Abdul Rahman; Ahmad Rusyadi Jumat (Journal of Techno-Social, 2023)
Facility management services are essential for maintaining the effective functioning and safety of buildings. Soft facility management services aim to enhance the work environment by improving efficiency and safety. Poor toilet hygiene due to inadequate care poses a threat to human health and safety. The objectives are to measure the effect of public toilet cleanliness based on the number of people and to analyse the relationship between the level of toilet cleanliness and the number of people. Observation methods were employed to monitor the number of people and evaluate toilet cleanliness from 9:00 a.m. to 17:30 p.m. at R&R X and Y. Linear regression analysis were conducted to determine R2 values for each location and using a one-way ANOVA. The R2 values represent the relationship between the star rating and the number of people. The result shows the R2 valuesfor men’s and women’s toilets at R&R X on weekdays and weekends are R2 = 0.7643, R2 = 0.7784, R2 = 0.2479, and R2 = 0.2245. For men’s and women’s toilets at R&R Y on weekdays and weekends, R2 = 0.1733, R2 = 0.2583, R2 = 0.5591, and R2 = 0.6939. In conclusion, it was found that the R2 values on the men’s toilets at R&R X and the women’s toilets at R&R Y had a strong and moderate relationship to the number of people and star rating. Meanwhile, women’s toilets at R&R X and men’s toilets at R&R Y have a weak relationship between the number of people and the star rating. It important to maintain the cleanliness, user comfort and safety, as well as the overall satisfaction of use, to maintain 5-star rating to ensure thatusers who use public toilets feel comfortable.